Personality Traits and Sales Effectiveness: The Life Insurance Market in Poland - Andrzej Janowski (Journal of Entrepreneurship, Management and Innovation)

(untitled)
Within organizatons in industrialized countries, the quality of human resources tends to become a major issue on the path to achieving a compettve advantage. According to the author’s research, the implementaton of the fve-factor model of Costa and McCrae provides the soluton for the abovementoned problem. This artcle demonstrates the crucial utlity of the fve-factor model of Costa and McCrae in the context of life insurance industry eﬀectveness from both the theoretcal and practcal perspectves based on a case study of the four largest life insurance companies 796 most eﬀectve agents. Results imply the existence of a positve correlaton between the level of the selected personality traits intensites and the life insurance agent’s sales efciency. Moreover, as levels of the personality traits of “openness to experience,” “consciousness,” “agreeableness” and “neurotcism” are the predictors of life insurance company eﬀectveness, there are fundamentals for inducton to be appropriate for the whole retail fnancial sector human resources management system.